Relationship Between Pregnant Women’s Knowledge of Pregnancy Danger Signs and Compliance with Antenatal Care Visits at Primary Healthcare Facilities - Fony; Eki Nawang Wulandari; Parti; Hardianti HP. Alam; Sukmawati Anwar (Karya Kesehatan Siwalima, 2026)
Pregnancy is a physiological condition that may develop into complications if not monitored regularly through Antenatal Care (ANC) examinations. Limited maternal knowledge regarding danger signs during pregnancy can affect compliance with ANC visits, thereby increasing the risk of complications for both mother and fetus. This study aimed to analyze the relationship between maternal knowledge of pregnancy danger signs and compliance with ANC examinations. This study employed a quantitative analytical design with a cross-sectional approach. The study population consisted of all pregnant women in the working area of a healthcare facility, with 92 respondents selected using a purposive sampling technique. Data were collected using a knowledge questionnaire and an ANC compliance observation sheet. Data analysis was conducted using univariate and bivariate methods with the Chi-Square test at a significance level of α = 0.05. The results showed that most respondents had a good level of knowledge regarding pregnancy danger signs (48 respondents; 52.2%), and the majority were compliant with ANC examinations (61 respondents; 66.3%). Statistical analysis demonstrated a significant relationship between maternal knowledge regarding pregnancy danger signs and compliance with ANC examinations (p = 0.001). Pregnant women with better knowledge tended to demonstrate higher compliance with routine ANC visits. This study highlights the importance of strengthening maternal health education regarding pregnancy danger signs to improve compliance with ANC examinations and support the early prevention of pregnancy complications.